2020
DOI: 10.20524/aog.2020.0528
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis hyperemesis syndrome: an update on the pathophysiology and management

Abstract: Cannabis hyperemesis syndrome (CHS) is a form of functional gut-brain axis disorder characterized by bouts of episodic nausea and vomiting worsened by cannabis intake. It is considered as a variant of cyclical vomiting syndrome seen in cannabis users especially characterized by compulsive hot bathing/showers to relieve the symptoms. CHS was reported for the first time in 2004, and since then, an increasing number of cases have been reported. With cannabis use increasing throughout the world as the threshold fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 73 publications
0
55
0
Order By: Relevance
“…Although not entirely clear, it is hypothesized that the cyclic vomiting is due to a disequilibrium with the endocannabinoid system and the brainstem and hypothalamic-pituitary-adrenal axis after heavy cannabis use. 8 The duration, frequency, route, or potency of cannabis products used that leads to greater risk for developing this illness has not been determined. However, a review of more than 200 patients diagnosed with CHS revealed that daily use of cannabis was reported in 47.9% of the patients and weekly use in 19.4% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although not entirely clear, it is hypothesized that the cyclic vomiting is due to a disequilibrium with the endocannabinoid system and the brainstem and hypothalamic-pituitary-adrenal axis after heavy cannabis use. 8 The duration, frequency, route, or potency of cannabis products used that leads to greater risk for developing this illness has not been determined. However, a review of more than 200 patients diagnosed with CHS revealed that daily use of cannabis was reported in 47.9% of the patients and weekly use in 19.4% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The endocannabinoid system (ECS) receptors cannabinoid type 1 (CB1) and cannabinoid type 2 (CB2) are G-protein coupled receptors that act by inhibiting adenylate cyclase. Their endogenous ligands are compounds derived from arachidonic acid, including Anandamide (AEA) and 2-AG (arachidonolyglycerol) [15]. CB1 receptors are found throughout many bodily systems, including the heart, spleen, lungs and bladder, but their main sites of action are the gastrointestinal and neurological systems [16].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…There are rare case reports of long-term, heavy recreational cannabis use promoting severe nausea and vomiting, which is known as the cannabis hyperemesis syndrome. [59][60][61] The syndrome is associated with compulsive bathing behaviour and resolves on cessation of cannabis use. Cannabis hyperemesis syndrome appears to be mediated by THC, and there is no evidence of CBD causing the syndrome.…”
Section: Cannabis Hyperemesis Syndromementioning
confidence: 99%